Beginning Aspirations for the Toronto Journal of Theology - Slater, Peter (Toronto journal of theology, 2021)
The Toronto Journal of Theology succeeded the Canadian Journal of Theology when the latter folded into Studies in Religion/Sciences Religieuses. TJT is an official publication of the Toronto School of Theology, encouraging scholarly articles by faculty, students, and friends of the TST’s four departments—biblical, historical, theological, and pastoral—Festschrifts for retired faculty, and lectures by distinguished visitors. The first co-editors were Jean-Marc Laporte of Regis College; Joanne McWilliam, then of St. Michael’s College; Peter Slater, then of Wycliffe College; and Don Wiebe of Trinity College as managing editor.